A horvát országimázs és a gasztronómia = The Croatian country image and gastronomy - Gerdesics Viktória (Köztes-Európa : társadalomtudományi folyóirat, 2017)
Nowadays, tourist destinations are competing with each other for tourists, places of origin are fighting for being connected to the most positive associations, regions are striving to attract investors and every single state needs good international relations. These could be achieved in a much easier way with a well-designed country brand and a favourable country image. Territorial aspects of marketing are not new theoretical or practical approaches but against their instinctive early usage, today every country pays attention to conscious development of its country brand and the significance of image. Country brand of Croatia had a particular path over the past two and a half decades, crossing the Yugoslavian war and the country’s accession to the EU in 2013, sometimes as a Balkan state and sometimes not. Present study investigates the built up of the Croatian country brand and focuses on what role the gastronomy gets in this, adding to these the country image, as the mirror of the consumer’s side.